IMPLEMENTASI KEBIJAKAN PENERTIBAN KERAMBA JARING APUNG TERHADAP KONDISI SOSIAL EKONOMI PETANI KERAMBA JARING APUNG DI DESA TANJUNG BUNGA, PANGURURAN, KABUPATEN SAMOSIR - Nduru, Sri Selvia Julita; Pasaribu, Vera A; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This research examines the Implementation of Floating Net Cage Management Policies on the Socio-Economic Conditions of Floating Net Cage Farmers (Case Study in Tanjung Bunga Village, Pangururan, Samosir Regency). The aim of this research is to determine the impact of controlling floating net cages on the socio-economic conditions of farmers floating net cages in Tanjung Bunga Village, Pangururan, Samosir Regency. The type of research used in this study was qualitative research. The research location was in Tanjung Bunga Village, Pangururan, Samosir Regency. The data collection in this study was obtained using interview and documentation techniques and then processed into narrative form. The informants in this study were key informants, namely the Head Tanjung Bunga Village, the main informants were floating net cage farmers. The results of the data transcripts were analyzed by managing, preparing data, sorting, coding, interpreted then concluded. The results of this study concluded that there were pros and cons in this policy where floating net cage farmers objected to the control of floating net cages but on the other hand the control of floating net cages was also carried out to protect and preserve Lake Toba as an KSPN area.